Venetoclax combined with ATRA shows promising therapeutic potential for TFG:: RARA variant APL: a case report - Ouyang, Xianfeng; Yan, Jianguo; Hu, Su; Zhu, Wenfeng; Zhou, Qibao; Hu, Fei (Frontiers in Oncology, 2025)
Most cases of acute promyelocytic leukemia (APL) are driven by the PML::RARA fusion gene, which is sensitive to differentiation induction therapy comprising of all-trans retinoic acid (ATRA) and arsenic trioxide (ATO). Treatment with ATRA plus ATO has achieved remarkable clinical outcome in patients with typical APL. However, 5% of patients still died from relapsed/refractory disease, predominantly high-risk APL and variant APL. The diagnosis and treatment of variant APL remain challenging. Here, we report a case of TFG::RARA variant APL recognized by targeted RNA sequencing. The patient achieved a sustained complete response following treatment with venetoclax combined with ATRA. Currently, the overall survival (OS) of the patient has exceeded 30 months, and the progression-free survival (PFS) has reached 29 months. Our results suggest that venetoclax combined with ATRA may be an ideal treatment option for patients with TFG::RARA variant APL.